Molecular characterization of predominant Streptococcus pneumoniae serotypes causing invasive infections in Canada: the SAVE study, 2011–15. (2nd July 2018) - Golden, Alyssa R; Adam, Heather J; Karlowsky, James A; Baxter, Melanie; Nichol, Kimberly A; Martin, Irene; Demczuk, Walter; Van Caeseele, Paul; Gubbay, Jonathan B; Lefebvre, Brigitte; Levett, Paul N; Zahariadis, George; et al.
Abstract: Objectives: This study characterized the 11 most predominant serotypes of invasive Streptococcus pneumoniae infections collected by the annual SAVE study in Canada, between 2011 and 2015. Methods: A subset of the 11 most predominant serotypes (7F, 19A, 22F, 3, 12F, 11A, 9N, 8, 33F, 15A and 6C) collected by the SAVE study was analysed using PFGE and MLST, as well as PCR to identify pilus-encoding genes. WGS analyses were performed on a subset of the above isolates plus a random selection of background strains. Results: Of the predominant serotypes analysed, 7F, 33F and 19A were obtained more commonly from children <6 years of age, whereas 15A, 6C, 22F and 11A were more common in adults >65 years of age. Pneumococcal pilus PI-1 was identified in antimicrobial-susceptible serotype 15A (61/212) and <10% of 6C isolates (16/188). PI-2 was found in serotype 7F (683/701) and two-thirds of 11A isolates (162/241). Only serotype 19A-ST320 possessed both pili. Molecular and phylogenetic analyses identified serotypes 19A, 15A, 6C, 9N and 33F as highly diverse, whereas 7F, 22F and 11A demonstrated clonality. Antimicrobial resistance determinants were common within diverse serotypes, and usually similar within a clonal complex. Conclusions: Despite successful use of conjugate vaccines, S. pneumoniae remains a highly diverse organism in Canada. Several predominant serotypes, both antimicrobial susceptible and MDR, have demonstrated rapid clonal expansion or an increase in diversity. As S. pneumoniae continues to evolve in Canada, WGS will be a necessary component in the ongoing surveillance of antimicrobial-resistant and expanding clones.